(untitled) (Docentes 2.0 Journal, 2024)
Role Plays and the communicative approach are beneficial methodological strategies to improve oral production in English in students of different ages and educational levels. The research aimed to identify how the communicative approach supported by Role Plays influences a methodological strategy to improve the oral production in English of the eighth-grade students of the Agustina Ferro School in Ocaña, Norte de Santander, Colombia. The interpretive paradigm guided the methodology based on a qualitative approach with a descriptive and cross-sectional action research design. The sample consisted of 39 students, 14 boys and 25 girls. As instruments and techniques for collecting and analyzing information, a content analysis matrix and field diaries through observation and interviews were used. As an intervention proposal, a sequence of 5 sessions was designed with Role Plays in various everyday situations that allowed students to strengthen their oral production in English and their communicative competence. This pedagogical approach promotes the acquisition of practical knowledge of the language and stimulates students’ critical thinking, creativity, and adaptability in intercultural situations. Role Plays supported by the communicative approach offers an effective way to empower students with the oral skills necessary to function confidently and successfully in environments where English is a vital communication tool.